Comparative Nucleotide Sequence Analysis of Glycoprotein B, C, and G of Infectious Laryngotracheitis Virus Isolated in Egypt During 2016-2018 - Maha, AN Gamal; Soliman, YA; Eman, MS El-Nagar; Saad, M; El-Hady, M (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Infectious Laryngotracheitis (ILT) is an economically important disease of poultry, causing a high mortality rate and /or reduced eggproduction. Tracheas from sever morbid and recently died unvaccinated household chicken were subjected to PCR assay to detectthe presence of the virus through amplification of the glycoprotein B gene. All tested samples gave positive ctranging from 13.32 to25.53. Virus isolation was performed by inoculation—the processed tracheal swaps onto the chorioallantoic membrane. Positive pocklesion has been developed within 7 days post-inoculation. The pock lesions were subjected to PCR assay for amplification of both thefull-length glycoprotein B, C, and G for sequencing analysis. Positive amplicons migrating about 2600, 1250, and 890 bp were amplifiedcorresponding to the orf of gpB, gpC and gpG genes. Sequence alignment and phylogenetic tree revealed that all sequenced isolatesgave a high degree with wild type isolate of ILT and a high degree of genetic stability was clearly evident among strains isolated indifferent periods (2016-2018), indicating that these glycoproteins could be used as a vaccine candidate.
Keywords: Glycoprotein B; Glycoprotein C; Glycoprotein G; ILT; Surface glycoproteins